Cercidospora navarroi, a new species of lichenicolous fungus from the Central Himalayan region of India - Joshi, Yogesh; Bansal, Pooja; Yadav, Arjun Lal (Phytotaxa, 2022)
Cercidospora navarroi colonizing the thallus and the apothecial discs of Rinodina intermedia is described as new to science from India and is compared with C. exiguella, C. rinodinae, and C. cf. rinodinae which also colonize the lichen genus Rinodina.